Enhanced oral bioavailability of self-assembling curcumin–vitamin E prodrug-nanoparticles by co-nanoprecipitation with vitamin E TPGS. (1st November 2020) - Zhang, Huiyun; Chen, Baoding; Zhu, Yuan; Sun, Congyong; Adu-Frimpong, Michael; Deng, Wenwen; Yu, Jiangnan; Xu, Ximing
Abstract: Curcumin (CUR), a nontoxic natural compound with potent antitumor activity, was limited in clinical application due to its insolubility and exceedingly low bioavailability. In this study, a novel prodrug-nanoparticle (CSSV/TPGS-NPs) self-assembled by co-nanoprecipitation of CUR-s-s-vitamin E conjugate and d -alpha-tocopheryl polyethylene glycol 1000 succinate (vitamin E TPGS) was prepared in attempt to solve aforementioned obstacles. CSSV/TPGS-NPs showed smaller sizes and better stability compared with that of CUR-s-s-vitamin E conjugate prodrug-nanoparticles (CSSV-NPs). Significantly, the absorption constant and effective permeability of CSSV/TPGS-NPs in different intestinal tracts increased 1.31–2.78 times and 1.81–6.95 times than that of CUR suspension, respectively. Pharmacokinetic study in Sprague-Dawley (SD) rats demonstrated that orally administered CSSV/TPGS-NPs displayed a prolonged plasma circulation with 8.06-fold increase in relative bioavailability compared to that of the CUR suspension. Altogether, conjugation of hydrophobic native CUR with vitamin E to form CSSV/TPGS-NPs is a promising technology for sustained and controlled drug delivery of CUR with improved oral bioavailability in vivo .